2011
DOI: 10.1186/1477-7819-9-172
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression of CEACAM7 in precursor lesions of gastric carcinoma and its prognostic value in combination with CEA

Abstract: BackgroundThe significance of carcinoembryonic antigen-related cell adhesion molecule 7 (CEACAM7) expression in gastric carcinoma and precancerous lesions and its correlation with CEA expression has rarely been previously investigated.MethodsCEACAM7 and CEA expression was detected by immunohistochemistry in consecutive sections of 345 subjects with gastric carcinoma and precancerous lesions. Laser confocal analysis was performed to determine CEACAM7 and CEA localization. Correlation between CEACAM7 and CEA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Furthermore, our observation is in agreement with different studies, which showed that the expression of other subfamily members is often associated with tumor grade. In particular, in gastric cancer, CEACAM7 protein expression is more frequently found in poorly differentiated compared to well and moderately differentiated gastric carcinomas (32). Additionally, CEA and CEACAM6 expression in colorectal cancer correlates inversely with the degree of cellular differentiation (33).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our observation is in agreement with different studies, which showed that the expression of other subfamily members is often associated with tumor grade. In particular, in gastric cancer, CEACAM7 protein expression is more frequently found in poorly differentiated compared to well and moderately differentiated gastric carcinomas (32). Additionally, CEA and CEACAM6 expression in colorectal cancer correlates inversely with the degree of cellular differentiation (33).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) staining was performed as previously described [ 10 , 11 ]. The primary mouse monoclonal anti-CIAPIN1 antibody (dilution 1:800) was developed in our laboratory [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…One hypothesis is that the quantitative expression of CEA would be different according to epithelial subtypes. Although CEA is most well known to be expressed in colorectal cancer tissues that share the immunophenotype with intestinal-type IPMNs [28], it is also reported to be expressed in gastric cancer and precursor lesions of gastric cancer [29], and pancreatic ductal adenocarcinoma [30]. Thus, each epithelial subtype of IPMN might have the potential to express CEA.…”
Section: Pancreatobiliarymentioning
confidence: 99%